INVESTIGATING THE STATIONARY PROPERTIES OF COAL, NATURAL GAS, AND OIL CONSUMPTION: THE CASE OF FRAGILE FIVE COUNTRIES - (:unkn) unknown (My University, 2021)
We examine the stationarity properties of primary energy consumption for"Fragile Five" countries and assesses whether shocks on coal, natural gas, and oilconsumption are permanent or temporary. The findings suggest that shocks on coalconsumption are temporary for Brazil, South Africa, and Turkey, while are permanentfor India and Indonesia. Moreover, the effect of shocks on natural gas consumption istemporary for five fragile countries except for South Africa. Finally, it is found thatshocks on oil consumption are temporary for only India and Indonesia.

"Kırılgan Beşli" ülkeleri için birincil enerji tüketiminin birim kök özelliklerini analiz edip ve kömür, doğal gaz ve petrol tüketimi üzerindeki şokların kalıcı veya geçici olup olmadığı incelenmiştir. Bulgular, kömür tüketimi üzerindeki şokların Brezilya, Güney Afrika ve Türkiye için geçici, Hindistan ve Endonezya için kalıcı olduğunu göstermektedir. Ayrıca, şokların doğal gaz tüketimi üzerindeki etkisi Güney Afrika dışındaki beş kırılgan ülke için geçicidir. Son olarak, petrol tüketimindeki şokların sadece Hindistan ve Endonezya için geçici olduğu bulunmuştur.
KÖMÜR, DOĞAL GAZ VE PETROL TÜKETİMİNİN DURAĞANLIK ÖZELLİKLERİNİN İNCELENMESİ: KIRILGAN BEŞLİ ÖRNEĞİ